Innovation and School Leadership: Keys to Post-Pandemic Educational Recovery in Challenging Contexts - Obregón Reyes, Jennifer; Godoy Orellana, Claudia (PEM. Revista de Didáctica, Evaluación e Innovación, 2024)
The purpose of this paper is to analyze how school leadership can respond to post-pandemic educational challenges through the implementation of innovations that contribute to recover learning and address historical educational inequalities. From a critical approach and based on the case of Chile, the text identifies the impact of the pandemic on education, highlighting problems such as school backwardness, dropout and deterioration of mental health in vulnerable communities. As a result, it is proposed that leadership that drives educational innovation is essential to transform pedagogical and curricular management and promote effective recovery. However, it is imperative that public policies provide resources, autonomy, and training to achieve this, thus advancing toward a more equitable, fair, and resilient education.